2021
DOI: 10.9734/jpri/2021/v33i50a33402
|View full text |Cite
|
Sign up to set email alerts
|

To Determine the Frequency of Thrombocytopenia in Pre Eclamptic Presented at Isra University Hospital

Abstract: Objective: To determine the frequency of thrombocytopenia in pre-eclamptic women presented at Isra University Hospital Hyderabad. Patients and Methods: This cross sectional descriptive study of six months study was conducted at Isra university hospital from April 2019 to September 2019. All the patients between ≥18 - 45 years of age diagnosed preeclampsia were admitted and evaluated for thrombocytopenia. Results: During six month study period, total of 177 patients with preeclampsia were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…They are between the ages of 18 and 49.The mean age is almost similar with previous study. The frequency of thrombocytopenia increases in females with pregnancy induced hypertension as a local study reported that thrombocytopenia was present in 55.9% of all patient groups 9 . One more study reported that thrombocytopenia was seen in 39.2% among 153 females with PIH 23 .…”
Section: Discussionmentioning
confidence: 94%
“…They are between the ages of 18 and 49.The mean age is almost similar with previous study. The frequency of thrombocytopenia increases in females with pregnancy induced hypertension as a local study reported that thrombocytopenia was present in 55.9% of all patient groups 9 . One more study reported that thrombocytopenia was seen in 39.2% among 153 females with PIH 23 .…”
Section: Discussionmentioning
confidence: 94%